2023
DOI: 10.3389/fphys.2023.1179582
|View full text |Cite
|
Sign up to set email alerts
|

Gastric juice non-coding RNAs as potential biomarkers for gastric cancer

Abstract: Gastric cancer (GC), being one of the most common malignant human tumors, occupies the second position in the structure of mortality in men and women. High rates of morbidity and mortality in this pathology determine its extremely high clinical and social significance. Diagnosis and timely treatment of precancerous pathology is the main way to reduce morbidity and mortality, and early detection of GC and its adequate treatment improve prognosis. The ability to accurately predict the development of GC and start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…It is worth noting that despite the scarcity of studies on non-blood samples, molecules with diagnostic value have been detected, which could also be used in disease monitoring. These samples present potential value as a source of molecules for determining prognosis, treatment, or patient management[ 194 ]. As mentioned earlier, analyzing these fluids can offer heightened sensitivity as they are in direct proximity to tumor cells, potentially yielding distinct information from blood samples.…”
Section: Lb In Gcmentioning
confidence: 99%
“…It is worth noting that despite the scarcity of studies on non-blood samples, molecules with diagnostic value have been detected, which could also be used in disease monitoring. These samples present potential value as a source of molecules for determining prognosis, treatment, or patient management[ 194 ]. As mentioned earlier, analyzing these fluids can offer heightened sensitivity as they are in direct proximity to tumor cells, potentially yielding distinct information from blood samples.…”
Section: Lb In Gcmentioning
confidence: 99%
“…Based on keyword co-occurrence clustering, as well as the frequency and centrality of keywords, this study summarized three research hotspots in this field. Firstly, the role of miRNAs as biomarkers in GC is a hot topic (50,51). Many case-control studies have found that miRNAs [e.g., miR-21 (17,52), miR-106 (53), miR-129, miR-196 ( 54), miR-214 ( 55), miR-135 ( 56), miR-223 (57), miR-421 ( 21), and miR-584 (58)] with different expression levels in GC patients have potential diagnostic and prognostic value for GC compared to healthy subjects.…”
Section: Research Hotspotsmentioning
confidence: 99%
“…Many case-control studies have found that miRNAs [e.g., miR-21 (17,52), miR-106 (53), miR-129, miR-196 ( 54), miR-214 ( 55), miR-135 ( 56), miR-223 (57), miR-421 ( 21), and miR-584 (58)] with different expression levels in GC patients have potential diagnostic and prognostic value for GC compared to healthy subjects. However, most of them had small sample sizes and different schemes for collecting and processing blood samples, resulting in poor repeatability of results (51,59). Encouragingly, GASTRO Clear ™ , the world's first serum GC molecular diagnostic panel based on 12-miRNAs, has been approved and launched in Singapore in 2019, with detection sensitivity and specificity reaching 87% and 93.9%, respectively (60), greatly enhancing the detection rate of stage I and II of GC.…”
Section: Research Hotspotsmentioning
confidence: 99%
“…Lncrnas can also affect the progression of tumors by regulating the activity and function of proteins, affecting the interaction between proteins, or changing the spatial structure of proteins (Tan et al 2020 ). Other studies have shown that lncrnas can be used as prognostic markers and potential therapeutic targets for gastric cancer (Wang et al 2019 ; Zheng et al 2019 ; Gareev et al 2023 ; Hosseini et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%